Factors Influencing Self-management Behaviors among Ischemic Stroke Patients - Srirung, Wanwisa; Puwarawuttipanit, Wimolrat; Koositamongkol, Sarunya (Nursing Science Journal of Thailand, 2022)
Purpose: To study the influence of hope, rehabilitation motivation, family support, and fatigue on self-management behavior among ischemic stroke patients. Design: Correlational predictive research. Methods: The sample was comprised of 128 ischemic stroke patients, both males and females, aged 18 years or older who came for a follow-up appointment after discharge at the out-patient department, Prasat Neurological Institute between March and May, 2020. The questionnaires included the demographic characteristics, the Herth Hope Index, Stroke Rehabilitation Motivation Scale, Family Support Questionnaires, Fatigue Severity Scale, and Self-management Behavior questionnaire. Data were analyzed by using descriptive statistics and multiple regression analysis. Main findings: An average age of the sample was 62.58 years old (SD = 9.14), and 97.7% of them had self-management behaviors at a high level ( = 92.76, SD = 6.37). All of the independent variables explained 44.4% of the variance in self-management behavior (R2 = .44). The factors significantly influencing self-management behavior were motivation for rehabilitation, family support, and hope ( = .41, p < .001, = .24, p < .01 and = .19, p < .05) respectively. Even though fatigue did not demonstrate the prediction, the significant correlation with self-management behavior was found. Conclusion and recommendations: Hope, motivation for rehabilitation, and family support could affect self-management behavior. Thus, it is recommended that healthcare team should be aware of the importance of building hope and motivation for rehabilitation. Families should be engaged in a program development and encouragement for promoting self-management behavior of the patients, consequently leading to good quality of life after ischemic stroke.